Determinants of Muslim household basic needs consumption expenditures - Noorhaslinda Kulub Abd. Rashid,; Aslina Nasir,; Zuraini Anang,; Roseliza Mat Alipiah,; Rahmah Ismail,; Sanep Ahmad,; S. Shahida, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper focuses on current household expenditure in an environment characterised by a high cost of living and modernisation. In order to cope with the current economic situation, individual vary in their consumption levels and lifestyles. In this study, basic needs expenditure refers to four main groups of household expenditure, namely food, housing, transportation and communication given that they make up a significant part of total household expenditure. Furthermore, the different budget constraints that vary with income and location, the different expenditure patterns reflect how people are surviving in the current economic climate. This paper identifies the factors contributing to basic needs consumption comprising food, housing, transportation and communication. The econometric analysis using Seemingly Unrelated Regression Estimation (SURE) shows that these expenditures are largely determined by the total monthly spouse income (Inc) and total borrowing (Bor) for all consumption expenditures. The results with interaction term also revealed no difference in the basic needs expenditure of urban and rural households in Selangor and Kelantan. Based on the findings, households should be educated on consumerism and financial management for effective financial planning.